2015
DOI: 10.1002/lsm.22457
|View full text |Cite
|
Sign up to set email alerts
|

Violet 405 nm light: A novel therapeutic agent against β‐lactam‐resistant Escherichia coli

Abstract: We have successfully demonstrated a significant bacterial reduction using high intensity 405 nm light. Illustrating the efficacy of this technology against a β-lactam-resistant E. coli is especially relevant to the need for novel methods of sterilization in healthcare settings. These results suggest that VLT using 405 nm light could be a suitable clinical option for eradication of β-lactam-resistant E. coli. Visible light kills statistically significant concentrations of E. coli. Antibiotic-resistant Gram-nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…The abundance of porphyrins generated in microbial cells is the reason behind the more susceptibility of all six representative microbes to 405 nm aBL irradiation than 470 nm, in agreement with the previous study showing that foodborne pathogens Lactobacillus plantarum , S aureus and Vibrio parahaemolyticus were all more susceptible to 405 nm than 460 nm or 520 nm light irradiation . Apart from the six microbes tested, Klebsiella pneumoniae and Escherichia coli were also commonly detected in contaminated PLT concentrates and particularly sensitive to 405 nm aBL reported in the previous studies .…”
Section: Discussionmentioning
confidence: 84%
“…The abundance of porphyrins generated in microbial cells is the reason behind the more susceptibility of all six representative microbes to 405 nm aBL irradiation than 470 nm, in agreement with the previous study showing that foodborne pathogens Lactobacillus plantarum , S aureus and Vibrio parahaemolyticus were all more susceptible to 405 nm than 460 nm or 520 nm light irradiation . Apart from the six microbes tested, Klebsiella pneumoniae and Escherichia coli were also commonly detected in contaminated PLT concentrates and particularly sensitive to 405 nm aBL reported in the previous studies .…”
Section: Discussionmentioning
confidence: 84%
“…At an exposure of 133 J/cm 2 , reductions in log 10 CFU were 6.27 for E. coli , 6.10 for S. aureus , 5.20 for P. aeruginosa , and 6.01 for S. pneumoniae . In another study from the same group of authors, the investigators found that β-lactam-resistant E. coli , which is resistant to penicillins, cephamycin, and carbapenems, is sensitive to aBL inactivation (Rhodes et al, 2016). Over 6-log 10 CFU reduction of the β-lactam-resistant E. coli strain on agar plates was achieved after an exposure of 68 J/cm 2 aBL.…”
Section: Efficacy Of Antimicrobial Blue Light Inactivation Of Pathmentioning
confidence: 99%
“…Visible light therapy is currently FDA approved for use for acne vulgaris, and research is being done to determine its role in treating SSI and device associated Gram-negative infections. An in vitro study evaluating the efficacy of violet 405nm light in treating ampicillin resistant Escherichia coli found an 81.7% reduction of bacterial growth with irradiance of 2.89 mW/cm 2 over 120 min (p < 0.001) [56]. Similarly, a review of both Gram-positive and Gram-negative bacteria susceptibility to violet light therapy between 380 and 480 nm found a 91% inactivation of Pseudomonas aeruginosa with 405 nm of VLT [57].…”
Section: Other Therapeutic Approachesmentioning
confidence: 99%